EMERGENCE OF NEOLITHIC IN THE SOUTHERN PLAINS OF IRAN: DARAB PLAIN - Ханипур, Мортеза (History, Archeology and Ethnography of the Caucasus, 2025)
The study of the Neolithic period in Southwest Asia, particularly the Zagros region, has been a central focus for archaeologists. However, while central Zagros has been extensively researched, the southern plains and valleys remained largely unexplored until approximately a decade ago. The diverse environmental characteristics of Fars province necessitated more detailed studies of each region. The current study focuses on the southern Zagros region to further investigate the Neolithic period. In 2019, the first survey season was conducted in Darab to identify archaeological settlements. A total of 351 sites, ranging from the Paleolithic to the Islamic periods, were discovered. The study presents an overview of the Neolithic period in the Darab plain, encompassing Neolithic sites, lithic tools, grinding stones, and pottery. Furthermore, the study aims to determine the factors that prompted Neolithic people to settle in the southern Zagros valleys and this region. Finally, it aims to define the role of this region in the Neolithization and development process on the Iranian Plateau. The survey results identified one site and one rock shelter with Pre-Pottery Neolithic evidence, including bullet cores and blades. This site represents the southernmost known Pre-Pottery Neolithic site in the Zagros. De Miroschedji identified Bizdan pottery as the oldest Neolithic pottery in the region, while four distinct pottery types have been recognized in Fars. During the latest Neolithic phase, coarse plain pottery was found in the Darab plain and other areas of Fars.
Keywords: Neolithic; Fars; Darab; sedimentary settlements; agriculture